A novel two-dimensional material B2S3 and its structural implication to new carbon and boron nitride allotropes. Issue 38 (8th September 2015) - Liu, Wei; Miao, Maosheng; Liu, Jing-yao
Abstract : We propose a single layer of B2 S3 as a new potential 2D material, conceived directly from its existing layered 3D crystal. New 2D BN and graphene allotropes are constructed from B2 S3 . Abstract : Two-dimensional (2D) semiconductor materials and the fabrication of related devices have become a new focus of electronics and materials science recently. Compared with three-dimensional (3D) semiconductors, the choice of 2D materials is very limited. Recently, the emerging goal of fabricating functional heterojunctions of 2D semiconductors has spurred a strong need to search for 2D materials that have a large variety of band gaps and band edges. Here, we propose a single layer of B2 S3 as a new potential 2D material, conceived directly from its existing layered 3D crystal. Using an advanced hybrid functional method, we demonstrated that 2D B2 S3 has a gap of 3.75 eV, filling a missing energy range for 2D materials. Furthermore, by adding extra B atoms at the 'vacancy' sites of the B2 S3 structure to give a 1 : 1 stoichiometry, we constructed new 2D BN and graphene allotropes that show large variation in the electronic structure. The BN allotrope exhibits a gap that is 0.99 eV lower than h-BN. Although the structure is significantly different to graphene, the new C allotrope contains a Dirac cone. However, the Dirac point is slightly lower than the Fermi level because of the electron transfer from an adjacent valence band to the Dirac cone states, resulting in a metallic state with both 'massless' electrons and massive holes.